2010
DOI: 10.1111/j.1467-629x.2010.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Distance to default, subordinated debt, and distress indicators in the banking industry*

Abstract: The recent financial crisis has highlighted the inadequacy of present supervisory arrangements to identify reliable ex-ante indicators of banking distress. For a sample of US bank holding companies, we analyse the extent to which distance to default based on market data can be explained using accounting-based indicators of risk. We show that a larger number of bank fundamentals help predict default for institutions that issue subordinated debt. For banks that issue subdebt, we find that higher charter values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
1
3
0
2
Order By: Relevance
“…Table 2 shows the results of OLS regression analysis of the banking sector factor measured by concentration in market and P/E ratio and found there is a significant impact of P/E ratio on financial banking stability at 5% significant level (sig = 0.018) at t-value = -2.471, with correlation 36.4%.The results can be explained that the banking sector is working in an integrated and coherent with each other within the monetary policy determined by the government through the central bank and reflected positively on P/E ratio contributed so effectively to achieve financial stability. This study consistent with Kato and Hagendorff (2010) related to nature of banking operation, that's mean related to market and study of Berger, et.al (2009) about the concentration in market Source: OLS regression analysis test from SPSS program. Table 3 shows the results of OLS regression of analysis the macroeconomic factor measured by inflation and GDP growth and found all variables insignificant impact of on financial banking stability.…”
Section: Analysis Of Ols Regression Of Each Independent Variablesupporting
confidence: 67%
“…Table 2 shows the results of OLS regression analysis of the banking sector factor measured by concentration in market and P/E ratio and found there is a significant impact of P/E ratio on financial banking stability at 5% significant level (sig = 0.018) at t-value = -2.471, with correlation 36.4%.The results can be explained that the banking sector is working in an integrated and coherent with each other within the monetary policy determined by the government through the central bank and reflected positively on P/E ratio contributed so effectively to achieve financial stability. This study consistent with Kato and Hagendorff (2010) related to nature of banking operation, that's mean related to market and study of Berger, et.al (2009) about the concentration in market Source: OLS regression analysis test from SPSS program. Table 3 shows the results of OLS regression of analysis the macroeconomic factor measured by inflation and GDP growth and found all variables insignificant impact of on financial banking stability.…”
Section: Analysis Of Ols Regression Of Each Independent Variablesupporting
confidence: 67%
“…Studies have demonstrated the ability of DD measures to predict default risk (Elton et al ., ; Gropp et al ., ; Vassalou and Xing, ). Kato and Hagendorff () analyze the extent to which distance to default based on market data can be explained using accounting‐based indicators of risk for a sample of U.S. bank holding companies. They show that a large number of bank fundamentals help to predict default for institutions that issue subordinated debt.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the subordinated debt variable in Table ( see columns 2 and 5 ), a larger proportion of subordinated debt is associated with larger charter value, consistent with the disciplining role of the subordinated debt (Kato and Hagendorff, ). This finding is not only statistically but also economically significant.…”
Section: Resultsmentioning
confidence: 63%